2019
DOI: 10.1088/1755-1315/343/1/012208
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing of puzzle local culture-based in teaching english for young learners

Abstract: Local culture-based learning is potential learning with integrates and emphasizes culture locally in the learning process. Learning through culture could be raised up of students’ appreciation for the local culture. This study potentials to improve students’ interesting, enrich vocabulary, metacognitive, and four basic language skills for younger learners “it is time to speak, it is time read, it is time to read, and the last one, time to listen. The subjects of this study were students’ primary school level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…This has led to an increased understanding of students in the higher experimental group. This is in line with the opinion [26]; [27]; [28]; [29] which states that learning by practicing will make it easier for students to understand the material and remember it for a longer time.…”
Section: Resultssupporting
confidence: 84%
“…This has led to an increased understanding of students in the higher experimental group. This is in line with the opinion [26]; [27]; [28]; [29] which states that learning by practicing will make it easier for students to understand the material and remember it for a longer time.…”
Section: Resultssupporting
confidence: 84%
“…furthermore, their confident will be shaped gradually to be better. In accordance with this finding, Butarbutar et al (2019) also found that learning English by using the local culture contents could make the students become more enthusiastic and motivated in the learning process. Besides that, by using local culture in learning English, it could improve the students' writing skills (Nurlia & Arini, 2017), speaking skills (Alakrash et al, 2021;Kamilah et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…By providing local cultural content in foreign language classes can also be easier to motivate the learner to explore their knowledge more and be more enthusiastic in class (Fu, 2018;Simamora, Saragih & Hasratuddin, 2018). In line with this, Butarbutar et al (2019) in their study was conducted at YPK elementary school Merauke-Papua, they found that the students were more motivated, energetic, and enthusiastic in learning English by local culture contents. Meanwhile, Alakrash et al (2021) and Kamilah, Fauziyah, Salsabila and Hidayat, (2019) found that the learners who are still at the beginning level can be easier to speak English using local words from their community.…”
Section: Introductionmentioning
confidence: 80%
“…[11] asserts the using WhatsApp application is effective to ameliorate students' reading ability. Contrary with [12] conclude in the midst of the rise of super modern technological advances today it is precisely the local culture-based learning that needs to be passed on to the younger generation. it aims to introduce and pass down the diversity of local culture to the younger generation as the nation's successors.…”
Section: Third Cyclementioning
confidence: 93%